Do Lifestyle Interventions Mitigate the Oxidative Damage and Inflammation Induced by Obesity in the Testis? - Ruben J. Moreira; Pedro F. Oliveira; Maria Angélica Spadella; Rita Ferreira; Marco G. Alves (Antioxidants)
Obesity results from a disproportionate accumulation of fat and has become a global health concern. The increase in adipose tissue is responsible for several systemic and testicular changes including hormone levels (leptin, adiponectin, testosterone, estrogen), inflammatory cytokines (increase in TNF-α and IL-6 and decrease in IL-10), and redox state (increase in reactive oxygen species and reduction in antioxidant enzymes). This results in poor sperm quality and compromised fertility in men with obesity. Lifestyle modifications, particularly diet transition to caloric restriction and physical exercise, are reported to reverse these negative effects. Nevertheless, precise mechanisms mediating these benefits, including how they modulate testicular oxidative stress, inflammation, and metabolism, remain to be fully elucidated. The main pathway described by which these lifestyle interventions reverse obesity-induced oxidative damage is the Nrf2-SIRT1 axis, which modulates the overexpression of antioxidant defenses. Of note, some of the detrimental effects of obesity on the testis are inherited by the descendants of individuals with obesity, and while caloric restriction reverses some of these effects, no significant work has been carried out regarding physical exercise. This review discusses the consequences of obesity-induced testicular oxidative stress on adult and pediatric populations, emphasizing the therapeutic potential of lifestyle to mitigate these detrimental effects.